Pendampingan Manajemen Keuangan dan Bisnis dalam Pengembangan Agribisnis di Pondok Pesantren CEO Bogor - Aziz, Abdul; Firmansyah, Rangga (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Islamic boarding schools as traditional Islamic educational institutions play a role in maintaining and developing religious values, cultural heritage, and character education. Pesantren have great potential in entrepreneurship development, one of which is agribusiness. However, agribusiness entrepreneurship development in pesantren offers opportunities to overcome the economic challenges faced by pesantren, such as limited financial resources and dependence on external donations. The purpose of this community service is to provide an understanding of managing finances and developing businesses Through the Participatory Action Research (PAR) approach, this assistance will involve santri as active participants to understand, develop the potential or assets owned by santri and boarding schools. Overall, the training participants, namely students, managers, staff, and boarding school administrators, already knew/understood about financial and business management. Of the 30 participants, including 100% of the students of the Bogor CEO boarding school who were able to complete the preparation of financial reports and analyse financial ratios, but data interpretation still reached 85%. Suggestions that can be given from the results of the service are: We recommend that the management of the Bogor CEO boarding school be more careful in the use of funds, acquisition of funds and assets and must be very careful with business development and business competition